RESPONS PRODUKSI CABAI RAWIT (Capsicum frutescens L.) TERHADAP WAKTU PEMANGKASAN DAN KONSENTRASI SITOKININ - Lulu Fatikhatul Maryamah (Muria Jurnal Agroteknologi (MJ-Agroteknologi), 2026)
This study aimed to evaluate the effects of shoot pruning time and cytokinin concentration on the growth and yield of bird’s eye chili (Capsicum frutescens L.). The experiment was conducted in Undaan Tengah Village, Undaan District, Kudus Regency, from September 2023 to January 2024. A factorial Randomized Complete Block Design (RCBD) with two factors and three replications was employed. The first factor was shoot pruning time (P), consisting of three levels: no pruning (P0), pruning at 15 days after planting (DAP) (P1), and pruning at 30 DAP (P2). The second factor was cytokinin concentration (S), consisting of three levels: no cytokinin application (S0), 25 ppm cytokinin (S1), and 50 ppm cytokinin (S2). The observed data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that shoot pruning time significantly affected the number of branches, days to flowering, fresh fruit weight per plant, and number of fruits per plant. In contrast, cytokinin application had no significant effect on all observed parameters. No interaction effect was observed between the two treatments.